Causes of death in Vanuatu. Issue 1 (December 2016) - Carter, Karen; Tovu, Viran; Langati, Jeffrey; Buttsworth, Michael; Dingley, Lester; Calo, Andy; Harrison, Griffith; Rao, Chalapati; Lopez, Alan; Taylor, Richard
Abstract Background The population of the Pacific Melanesian country of Vanuatu was 234, 000 at the 2009 census. Apart from subsistence activities, economic activity includes tourism and agriculture. Current completeness of vital registration is considered too low to be usable for national statistics; mortality and life expectancy (LE) are derived from indirect demographic estimates from censuses/surveys. Some cause of death (CoD) data are available to provide information on major causes of premature death. Methods Deaths 2001–2007 were coded for cause (ICDv10) for ages 0–59 years from: hospital separations (HS) (n = 636), hospital medical certificates (MC) of death (n = 1, 169), and monthly reports from community health facilities (CHF) (n = 1, 212). Ill-defined causes were 3 % for hospital deaths and 20 % from CHF. Proportional mortality was calculated by cause (excluding ill-defined) and age group (0–4, 5–14 years), and also by sex for 15–59 years. From total deaths by broad age group and sex from 1999 and 2009 census analyses, community deaths were estimated by deduction of hospital deaths MC. National proportional mortality by cause was estimated by a weighted average of MC and CHF deaths. Results National estimates indicate main causes of deaths <5 years were: perinatal disorders (45 %) and malaria, diarrhea, and pneumonia (27 %). For 15–59 years, main causes of male deaths were: circulatory disease 27 %, neoplasms 13 %, injury 13 %, liver disease 10 %, infection 10 %, diabetes 7 %, and chronic respiratory disease 7 %; and for females: neoplasms 29 %, circulatory disease 15 %, diabetes 10 %, infection 9 %, and maternal deaths 8 %. Infection included tuberculosis, malaria, and viral hepatitis. Liver disease (including hepatitis and cancer) accounted for 18 % of deaths in adult males and 9 % in females. Non-communicable disease (NCD), including circulatory disease, diabetes, neoplasm, and chronic respiratory disease, accounted for 52 % of premature deaths in adult males and 60 % in females. Injuries accounted for 13 % in adult males and 6 % in females. Maternal deaths translate into an annual maternal mortality ratio of 130/100, 000 for the period. Conclusion Vanuatu manifests a double burden of disease with significant proportional mortality from perinatal disorders and infection/pneumonia <5 years and maternal mortality, coupled with significant proportional mortality in adults (15–59 years) from cardiovascular disease (CVD), neoplasms, and diabetes.